A Custom EOG-Based HMI Using Neural Network Modeling to Real-Time for the Trajectory Tracking of a Manipulator Robot - Perez Reynoso, Francisco D.; Niño Suarez, Paola A.; Aviles Sanchez, Oscar F.; Calva Yañez, María B.; Vega Alvarado, Eduardo; Portilla Flores, Edgar A. (Frontiers in Neurorobotics, 2020)
Although different physiological signals such as Electrooculography (EOG) have been widely used in the control of assistance systems for people with disabilities, customizing the signal classification system remains a challenge. In most interfaces, the user must adapt to the classification parameters, although ideally, the systems must adapt to the user parameters. Therefore, in this work is presented the use of a Multilayer Neural Network (MNN) to model the EOG signal as a mathematical function, which is optimized using genetic algorithms, in order to obtain the maximum and minimum amplitude threshold of the EOG signal of each person that uses the designed interface. The problem of the variation of the voltage threshold of the physiological signals is addressed by means of an intelligent calibration, if an assistance system is not calibrated it loses functionality. Artificial intelligence techniques such as machine learning and fuzzy logic are used for classification of the EOG signal, but they need calibration parameters that are obtained through databases generated through prior user training, depending on the effectiveness of the algorithm, the learning curve and the response time of the system. In this work, by optimizing the parameters of the EOG signal, the classification is customized and the domain time of the system is reduced without the need for a database and the training time of the user is minimized, significantly reducing the time of the learning curve. The results are implemented in an HMI for the generation of points in a Cartesian space ( , , ) in order to control a manipulator robot that follows a desired trajectory by means of the movement of the user's eyeball.